Leading with Prophetic Integrity: Strengthening Islamic Education through Shiddiq, Amanah, and Fathanah - Zahrotunnisa` Siswahyuningsih; Ndanda Ambarawadi; Jaswadi; Abd Aziz; Nur Efendi (Managere: Indonesian Journal of Educational Management, 2025)
This research aims to explore the implementation of the prophetic values of shiddiq (honesty), amanah (responsibility), and fathanah (wisdom) in the leadership of Islamic education in madrassas in Indonesia. Using a qualitative approach with an intrinsic case study design, data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using Miles and Huberman's interactive model. The results of the study show that the value of shiddiq is realized through budget transparency, consistency of actions, and open policy delivery, which strengthens trust and fosters an honest work culture. The value of the mandate is realised through systematic supervision, competency-based task distribution, open reporting, and collective deliberation, resulting in a credible and accountable work system. Meanwhile, Fathanah is reflected in data-driven strategic decision-making, participatory dialogue, and wise responses to crises, which increase organizational efficiency and participation. These three values contribute significantly to building ethical, transformative, and benefit-oriented leadership. This research strengthens the position of prophetic leadership as a strategic framework in contemporary Islamic education governance, while offering an applicative model for the development of competencies of madrasah heads.